Procrastination, Flow, and Academic Performance in Real Time Using the Experience Sampling Method. Issue 3 (4th May 2018) - Sumaya, Isabel C.; Darling, Emily
ABSTRACT: The authors' aim was to first provide an alternative methodology in the assessment of procrastination and flow that would not reply on retrospective or prospective self-reports. Using real-time assessment of both procrastination and flow, the authors investigated how these factors impact academic performance by using the Experience Sampling Method. They assessed flow by measuring student self-reported skill versus challenge, and procrastination by measuring the days to completion of an assignment. Procrastination and flow were measured for six days before a writing assignment due date while students ( n = 14) were enrolled in a research methods course. Regardless of status of flow, both the nonflow and flow groups showed high levels of procrastination. Students who experienced flow as they worked on their paper, in real time, earned significantly higher grades ( M = 3.05 ± 0.30: an average grade of B) as compared with the nonflow group ( M = 1.16 ± 0.33: an average grade of D; p = .007). Additionally, students experiencing flow were more accurate in predicting their grade (difference scores, flow M = 0.12 ± 0.33 vs. nonflow M = 1.39 ± 0.29; p = .015). Students in the nonflow group were nearly a grade and a half off in their prediction of their grade on the paper. To the authors' knowledge, the study is the first to provide experimental evidence showing differences in academic performance between students experiencing flow and nonflow students.